The admiral was a lady - Rogell, Albert, 1901-1988; O'Brien, Edmond, 1915-1985; Hendrix, Wanda, 1928-1981; Roxbury Productions Inc.; Cinetel Films ([Los Angeles, CA] : Roxbury Productions, 1950)
Wanda Hendrix plays a WAVE officer who is endlessly pursued by ex-airmen Edmond O'Brien, Johnny Sands, and Steve Brodie. However, Hendrix only has eyes for her boyfriend Dick Erdman, who is on the lam from vengeful millionaire Rudy Vallee. --
Edmond O'Brien, Wanda Hendrix, Rudy Vallee, Steve Brodie, Johnny Sands, Richard Erdman, Hilary Brooke, Richard Lane, Garry Owen, Fred Easler.
Photography, Stanley Cortez; editor, William Ziegler; music, Edward J. Kay.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 8, 2015)
Keywords: Comedy films; Feature films; Internet videos; Streaming video